2022
DOI: 10.3390/v14102203
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy Skin Disease Outbreaks in Africa, Europe, and Asia (2005–2022): Multiple Change Point Analysis and Time Series Forecast

Abstract: LSD is an important transboundary disease affecting the cattle industry worldwide. The objectives of this study were to determine trends and significant change points, and to forecast the number of LSD outbreak reports in Africa, Europe, and Asia. LSD outbreak report data (January 2005 to January 2022) from the World Organization for Animal Health were analyzed. We determined statistically significant change points in the data using binary segmentation, and forecast the number of LSD reports using auto-regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The major finding of our study included the fact that the Nigerian LSDV isolates were similar to other known African isolates from Sudan, Ethiopia, South Africa, and Egypt, and European isolates from Bulgaria, Greece, Serbia, Turkey, and isolates from Russia, Kazakhstan, Iraq, and Israel, but different from recombinant LSDV field isolates from China, Thailand, Taiwan, and Russia [ 66 ]. On the other end, the Nigerian PCPV isolates were clustered with the Zambian and Botswana isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding of our study included the fact that the Nigerian LSDV isolates were similar to other known African isolates from Sudan, Ethiopia, South Africa, and Egypt, and European isolates from Bulgaria, Greece, Serbia, Turkey, and isolates from Russia, Kazakhstan, Iraq, and Israel, but different from recombinant LSDV field isolates from China, Thailand, Taiwan, and Russia [ 66 ]. On the other end, the Nigerian PCPV isolates were clustered with the Zambian and Botswana isolates.…”
Section: Discussionmentioning
confidence: 99%
“…To identify significant changes in rabies occurrences during the period from 2005 to 2018, change point analysis was applied to the obtained dataset [ 38 , 46 , 47 ]. These occurrences were assumed to follow the Poisson distribution due to the count nature of the data.…”
Section: Methodsmentioning
confidence: 99%
“…Time series analysis relies on previous data to uncover the underlying time-dependent structure and project future trends [ 37 ]. On the other hand, change point analysis detects sudden structural changes in time series analysis, providing factual context for the trend [ 38 ]. Recently, numerous epidemiological studies have used a variety of time-series techniques to create prediction models that can be used with a wide range of data [ [39] , [40] , [41] ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the two organizations focused on the LSD outbreak in the Balkan and Caucasus countries [ 12 ]. On the other hand, epidemiological aspects and control strategies related to LSD in Asian countries remain to be analyzed, even though some studies have been done and reported [ 1 2 3 4 8 13 ].…”
Section: Lsd Control Strategies By Country With the Outbreakmentioning
confidence: 99%